International law before municipal courts: the role of International Court of Justice decisions in domestic court proceedings with specific reference to United States case examples - Mangezi, Mutsa (Rhodes University, Faculty of Law, Law, 2008)
In the case of LaGrand (Germany v United States), the International Court of Justice held that the United States (US) had violated its international obligation to Germany under the Vienna Convention on Consular Relations when it executed two German nationals without first informing them of their consular rights. The case came before the court after the United States had disregarded a preliminary ruling passed by the IC], which directed the US not to execute the German nationals pending the outcome of the ICJ case. The decision raised the issue of the effect of ICJ decisions in domestic proceedings and the effectiveness of ICJ enforcement mechanisms. This thesis considers the possibility of a role for national courts as active enforcers of ICJ decisions. It is argued that whilst evidence shows that there is no legal obligation on courts to enforce ICJ decisions, there is certainly room in international law to facilitate this development. In support of this argument, the thesis demonstrates how basic presuppositions about international law have shifted over the last few decades. This shift has been both the impetus and the result of globalisation. The case of LaGrand alongside similar cases is used to show how national courts may play an increased role in the enforcement of ICJ decisions.
Keywords: International Court of Justice -- Cases; Vienna Convention on Consular Relations (1963); International and municipal law -- United States -- Cases; International law -- United States -- Cases; Jurisdiction (International law) -- Cases